Physical activity buffers the negative relationship between multimorbidity, self-rated health and life satisfaction - Marques, Adilson (2018)
Background: This study aimed to examine the relationship between multimorbidity, self-rated health and life satisfaction, and to test the moderating effect of physical activity on the relationship between multimorbidity, self-rated health and life satisfaction. Methods: This is a cross-sectional study based on data from the European Social Survey 2014. Participants were 25 713 adults (12 830 men), aged 18-64 years old, from 18 European countries and Israel. Self-reported information regarding chronic diseases, health perception, life satisfaction and physical activity was collected through interview. Multimorbidity was defined as the co-occurrence of ≥ 2 chronic diseases. Linear regression models were used to estimate the effects of multimorbidity, physical activity and the interaction effect of multimorbidity × physical activity on self-rated health and life satisfaction. Results: Multimorbidity was negatively related to self-rated health (d = 0.03) and life satisfaction (d = 0.03). Physical activity was positively related to self-rated health and life satisfaction. There was a significant interaction effect between multimorbidity and physical activity with regard to self-rated health (β = 0.01, P < 0.001) and life satisfaction (β = 0.04, P < 0.001). Conclusions: Physical activity buffered the negative relationship between multimorbidity, self-rated health and life satisfaction; contributing to better self-rated health and life satisfaction.